Peranan Guru Dalam Mengimplementasikan Kurikulum Pembelajaran - Sukmawati, Henny (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2023)
In the learning process the role of the teacher determines student learning outcomes. Therefore, the main role of the teacher at school is to convey knowledge as a past cultural heritage which is considered useful so that it must be preserved, so that the teaching process that is the responsibility is more successful, the role of the teacher as a source of learning is related to mastery of learning material, however great the progress technology, the teacher's role will still be needed in implementing it, thanks to the teacher's expertise, the curriculum has meaning and value. This means that through the teacher the values ​​contained in the curriculum can be conveyed to students, and the actualization and transformation of values, attitudes, knowledge and skills contained in the curriculum/syllabus is carried out by the teacher through curriculum implementation, namely the real or actual curriculum.